PROSES PENGEMBANGAN MEDIA FLASHCARDS BERORIENTASI KEARIFAN LOKAL UNTUK PEMBELAJARAN BAHASA INDONESIA PENUTUR ASING (BIPA) UNESA - HAJJAH, RIKA ROFI’ATUL; MINTOWATI, MINTOWATI; INDARTI, TITIK (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research aims to describe the process of developing local wisdom-oriented flashcard media for learning speaking skills integrated with writing and reading skills in Indonesian for Foreign Speakers (BIPA) at Surabaya State University and to describe the quality of local wisdom-oriented flashcard media for learning Indonesian for Foreign Speakers (BIPA) at State University Surabaya. Development research focuses on product development. The product developed in this research is flashcards learning media. This research approach is mixed methods. The research model in this development research uses the Addie research model. This research procedure uses the ADDIE development model. The ADDIE development procedure has five procedures, namely Analysis, Design, Development, Implementation and Evaluations. The results obtained in the development of East Java local wisdom-oriented flashcards media in speaking learning integrated with reading and writing for Indonesian Language and Foreign Speakers (BIPA) students at the Faculty of Languages ??and Arts, Surabaya State University resulted in the conclusion that East Java local wisdom-oriented flashcard media can be used in learning spoke about BIPA because it had carried out a series of ADDIE development stages which were based on needs analysis. ADDIE's stages in developing flashcards media are analysis, design, development, implementation and evaluation. Based on the five development stages, flashcards media has gone through the evaluation stage, namely changing or improving according to the direction of the validator. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan proses pengembangan media flashcards berorientasi kearifan lokal untuk pembelajaran keterampilan berbicara berintegrasi keterampilan menulis dan membaca Bahasa Indonesia Penutur Asing (BIPA) Universitas Negeri Surabaya dan mendeskripsikan kualitas media flashcards berorientasi kearifan lokal untuk pembelajaran Bahasa Indonesia Penutur Asing (BIPA) Universitas Negeri Surabaya. Penelitian pengembangan berfokus pada pengembangan produk. Produk yang dikembangkan dalam penelitian ini yakni media pembelajaran flashcards. Pendekatan penelitian ini yakni mixed methods. Model penelitian dalam penelitian pengembangan ini yakni menggunakan model penelitian Addie. Prosedur penelitian ini menggunakan model pengembangan ADDIE. Prosedur pengembangan ADDIE memiliki lima prosedur yakni Analysis, Design, Development, Implementation and Evaluations. Hasil yang diperoleh dalam pengembangan media flashcards berorientasi kearifan lokal Jawa Timur pada pembelajaran Berbicara berintegrasi membaca dan menulis peserta didik Bahasa Indonesia Penutur Asing (BIPA) Fakultas Bahasa dan Seni, Universitas Negeri Surabaya menghasilkan simpulan yakni media flashcards berorientasi kearifan lokal Jawa Timur dapat digunakan dalam pembelajaran berbicara BIPA karena telah melakukan rangkaian tahapan pengembangan ADDIE yang dilandasi oleh analisis kebutuhan. Tahapan ADDIE dalam pengembangan media flashcards ini yakni analisis, desain, development, implementacion, dan evaluasi. Berdasarkan kelima tahapan pengembangan tersebut, media flashcards telah melalui hingga tahapan evaluasi yakni mengubah atau memperbaiki sesuai arahan validator.